Internal procedures, Trojan horses, and the right to deduct input VAT. Remarks concerning the judgment of the Supreme Administrative Court of 25 July 2017 (I FSK 1798/15) - Krzysztof Lasiński-Sulecki (Prawo Budżetowe Państwa i Samorządu, 2018)
According to the Supreme Administrative Court, Art. 86(1), Art. 88(3a) and Art. 99(12) of the Goods and Services Tax Act are to be interpreted as meaning that the introduction by the taxpayer of procedures for verifying suppliers and recipients of goods or services does not constitute good faith and, consequently, does not allow the right to deduct input tax on the basis of invoices which do not reflect actual economic events, if those procedures have not been followed in a transaction with a particular supplier or recipient.